Water, soap, and hand‐disinfectant exposure during the COVID‐19 pandemic and self‐reported hand eczema in frontline workers: A cross‐sectional study - Vilela, Libe; Lagrelius, Maria; Berglind, Ina Anveden; Midander, Klara; Schenk, Linda; Julander, Anneli (Contact dermatitis, 2024)
Background During the COVID‐19 pandemic, increased hand hygiene practices were implemented. Impaired skin health on the hands among healthcare workers has been reported previously. Knowledge of how worker in other occupations have been affected is scarce. Objectives To investigate self‐reported hand water‐, and soap exposure and use of hand disinfectants, and hand eczema (HE) in frontline workers outside the hospital setting and in IT personnel during the COVID‐19 pandemic. Methods In this cross‐sectional study, a questionnaire was sent out between 1 March and 30 April in 2021, to 6060 randomly selected individuals representing six occupational groups. Results A significant increase in water exposure and hand disinfectant use was shown: Relative position (RP) 19; 95% confidence interval (CI) 0.17–0.21 and RP = 0.38: 95% CI 0.36–0.41, respectively. Newly debuted HE was reported by 7.4% of the population, more frequently among frontline workers (8.6%) compared to IT personnel (4.9%). Conclusions Water and soap exposure and use of hand disinfectants increased during COVID‐19 pandemic, which may increase the risk of hand eczema. This highlights the importance of communication and implementation of preventive measures to protect the skin barrier also in occupations other than healthcare workers. Frontline workers in other occupations than health care and IT personnel reported significantly increased exposure to water, soap, and hand disinfectant during the COVID‐19 pandemic. Furthermore, 8.6% of the frontline workers and 4.9% of the IT personnel reported to have a newly debuted hand eczema during the pandemic.